Financing constraints, fixed capital and R&D investment decisions of belgian firms - Michele Cincera (National Bank of Belgium, 2002)
This paper aims at assessing the relationship between the possible existence of financial constraints and the decisions of Belgian private firms as regards their investments in both capital and R&D investments over the last decade. The main system GMM estimates from the error-correction equations indicate that the sensitivity of both types of investments to cash flow variations are rather differentiated. On the whole, these effects are more important for investments in ordinary assets, young small-scale firms located in the Walloon region that are not part of a multinational. Firms that perform R&D on a permanent basis and that receive public funds to support these activities appear to be less cash constraints.
Keywords: C23; E22; O31; 330; financial constraints; investments in capital and R&D; Belgian private companies; error-correction investment equations; system GMM panel data econometric models; Investitionsentscheidung; Betriebliches Anlagevermögen; Forschungskosten; Fremdkapital; Belgien